PENGEMBANGAN MULTIMEDIA UNTUK PEROLEHAN BELAJAR KONSEP PECAHAN DI KELAS III SDN 41 SUNGAI AMBAWANG - Mahdalena Mahdalena; Indri Astuti; Dede Suratman (Universitas Tanjungpura, 2017)
Abstract The main problem in this research is the difficulty of learning media procurement in math lesson especially on fractional concept material. Many learners have difficulty understanding fractions because learning tends to use a mechanistic way of giving rules directly to be memorized, remembered and applied, so that the fractional concepts will be quickly forgotten by learners and will be difficult to apply the concept. The results of this research are: (1) multimedia design is carried out through stages such as conducting preliminary research, designing, material collection, initial product development, material expert validation, media expert and design expert, (2) multimedia profile depicted in the storyboard contains the forms of drawings accompanied by explanations or narratives used in the process of producing multimedia programs, so that in the process of producing multimedia programs will be more structured and orderly, (3) the implementation of multimedia learning is done by students with enthusiasm, it looks more learners enthusiastic in the implementation of learning so that learners more independent and active, and (4 Learning outcomes of learners who use multimedia, this can be seen from the differences in learning results fractional concept between before learning and after learning to use multimedia. Keywords: Multimedia, Fractional Concept, Borg and Gall.